2019
DOI: 10.1136/postgradmedj-2018-136102
|View full text |Cite
|
Sign up to set email alerts
|

Association between ICAM-1 level and diabetic retinopathy: a review and meta-analysis

Abstract: Elevated levels of proinflammatory markers are evident in patients with diabetic retinopathy (DR) and are associated with disease progression and prognosis. Intercellular adhesion molecule-1 (ICAM-1) is involved in inflammation and acts as a local intensifying signal in the pathological processes associated with chronic eye inflammation. The aim of this systematic review and meta-analysis was to investigate the relationship between ICAM-1 level and DR. Online electronic databases were searched to retrieve all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Intercellular adhesion molecule-1 (ICAM-1) is a member of the immunoglobulin supergene family with the ability of cellular adhesion molecules mediating the attachment of lymphocytes. Diabetes retinopathy patients in a meta-analysis research showed that ICAM-1 expression was related to the severity of diabetes retinopathy and generally exists in patients [34]. Our results are also consistent with the pathology of diabetes retinopathy, showing a decrease of tight junction-related protein expression and increased ICAM-1 in the high glucose-and 4-HNE-induced retinopathy.…”
Section: Discussionsupporting
confidence: 87%
“…Intercellular adhesion molecule-1 (ICAM-1) is a member of the immunoglobulin supergene family with the ability of cellular adhesion molecules mediating the attachment of lymphocytes. Diabetes retinopathy patients in a meta-analysis research showed that ICAM-1 expression was related to the severity of diabetes retinopathy and generally exists in patients [34]. Our results are also consistent with the pathology of diabetes retinopathy, showing a decrease of tight junction-related protein expression and increased ICAM-1 in the high glucose-and 4-HNE-induced retinopathy.…”
Section: Discussionsupporting
confidence: 87%
“…ICAM-1 is mainly expressed by EC and leukocytes, following cytokine stimulation. Leukocytes are involved in the pathogenesis of many retinal diseases, among which DR [24], and their adhesion is regulated by ICAM-1 and MCP-1 [23,24]. ICAM-1 is also involved in angiogenesis, as VEGF can enhance its expression [24].…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytes are involved in the pathogenesis of many retinal diseases, among which DR [24], and their adhesion is regulated by ICAM-1 and MCP-1 [23,24]. ICAM-1 is also involved in angiogenesis, as VEGF can enhance its expression [24]. Increased MMP2 and MMP9 expression, and the concomitant reduction of TIMP1, as found in our cell models, are consistent with our previous findings showing dysregulation of the MMPs/TIMP1 system in HRPs due to high glucose damage [17], as well as increased MMP2 in the same cells exposed to extracellular vesicles released in diabetic-like conditions [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of DR hyperglycaemia is the causative factor, causing a series of reactions that include the increase in the production of catabolic products of glycosylation, the activation of the metabolism of the polyol pathway and the altered transduction of cellular signals (Yao et al, 2019). The damage to the pericytes, mesenchymal cells with contractile function that partially surrounds the endothelial cells, results in an imbalance in the mechanisms of regulation of flow controls with consequent hypoxia and accumulation of fluid inside the retinal tissue (Sinclair and Schwartz, 2019) as reported in this recent study.…”
Section: Mechanisms Underlying Diabetic Retinopathymentioning
confidence: 99%